Optimizing the Development of Agricultural Cooperatives through Rukun Tetangga (RT) Based Design - Sumantri, Bambang Agus; Raharjo, Itot Bian; Samari, Samari; Kurniawan, Rony; Ratnanto, Sigit (Journal of Community Service and Society Empowerment, 2024)
Indonesia is a country based on strong family, friendly, mutual cooperation with a cooperative economic system. Demand for the agricultural sector is increasing because agricultural products are not only used as food, but also as feed, fuel and fiber. The conclusion from this service is that the Rukun Tetangga (RT) level as a basic step in establishing agricultural cooperatives cannot yet be used, so further model development and community conditioning is needed. Individual farming and renting agricultural land in the micro category. Agricultural facilities and infrastructure are not optimal and the costs of the production process (input) are greater than the income from agricultural products (output) which is small. Farmers' agricultural business organization is not yet optimal.